2021
DOI: 10.3390/jcm10163723
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Obese and Non-Obese Children and Adolescents Regarding Their Oral Status and Blood Markers of Kidney Diseases

Abstract: (1) Background: A rarely discussed effect of obesity-related glomerulopathy (ORG) may slowly lead to irreversible glomerular damage and the development of chronic kidney disease. These patients need to undertake medical care, but whether they should be included in intensive oral care is still not mandatory. The study aimed to assess a relationship between renal, metabolic, and oral health indicators among pediatric patients affected by simple obesity. (2) Methods: 45 children and adolescents with simple obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
(61 reference statements)
1
1
0
5
Order By: Relevance
“…Blood urea and serum creatinine were within normal range with no substantial variations among obese children and controls (p=0.141), (p=0.354) and this comes in line with the study of Maćkowiak-Lewandowicz et al [27]. In contrary Khan et al, [28] study revealed that blood urea, serum creatinine was substantially elevated in obese group as contrasted to controls i.e.…”
Section: Assupporting
confidence: 85%
See 1 more Smart Citation
“…Blood urea and serum creatinine were within normal range with no substantial variations among obese children and controls (p=0.141), (p=0.354) and this comes in line with the study of Maćkowiak-Lewandowicz et al [27]. In contrary Khan et al, [28] study revealed that blood urea, serum creatinine was substantially elevated in obese group as contrasted to controls i.e.…”
Section: Assupporting
confidence: 85%
“…While LDL concentrations hadn't been substantial various among groups. However, Maćkowiak-Lewandowicz et al, [30] found that obese and control groups didn't vary in serum levels of total cholesterol and LDL. While substantially greater levels of HDL and TG (p = 0.001, p = 0.001).…”
Section: Asmentioning
confidence: 96%
“…Studi ini melaporkan bahwa LFG anak obes secara bermakna lebih rendah dibandingkan anak non-obes (73,10±22,33 mL/min/1,73 m 2 vs 85,30±32,25 mL/min/1,73 m 2 ), dengan nilai p=0,048. Hasil yang serupa juga didapatkan pada penelitian Maćkowiak-Lewandowicz et al, 12 Renda, 15 dan Mahayani et al,19. Ketiga penelitian tersebut mendapatkan LFG pada kelompok obes secara bermakna lebih rendah dibandingkan dengan kelompok berat badan normal (p=0,019; p= 0,05; p<0,001).…”
Section: Bahasanunclassified
“…Mahayani et al 19 melaporkan hal serupa, yakni tingkat frekuensi hipertensi lebih tinggi pada kelompok obes (p<0,001). Pada studi Maćkowiak-Lewandowicz et al 12 juga didapatkan 25 dari 45 anak obes mengalami hipertensi primer. Pada ketiga penelitian tersebut, LFG anak obes didapatkan secara bermakna lebih rendah dibandingkan dengan LFG anak normal.…”
Section: Bahasanunclassified
See 1 more Smart Citation